Implementasi Rational Unified Process dalam Perancangan Aplikasi Inventory Management Berbasis Web pada Astro Detailing Mobil - Jose Nasio; Hariyanto Wibowo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Astro Car Detailing is a vehicle maintenance service company that still manages inventory through ledgers and manual recording sheets. This condition poses risks of data loss, recording errors, discrepancies between physical stock and records, as well as delays in report preparation that can take up to three days. This research aims to design and build a web-based Inventory Management application to integrate inventory data management at Astro Car Detailing. The system development method uses the Rational Unified Process (RUP), which consists of the Inception, Elaboration, Construction, and Transition phases. Data is obtained through observation, interviews, and literature studies. The system is built using PHP with the CodeIgniter framework, MySQL database, and Unified Modeling Language (UML) modeling. Functional testing is conducted using Black Box Testing on the login function, category management, items, suppliers, users, incoming goods transactions, outgoing goods transactions, stock reports, and logout. The results show that the application successfully integrates master data and inventory transactions and generates stock information based on data stored in the system. All documented main functional scenarios produce outputs that meet the expected results. The implementation of the system accelerates the report preparation process, which previously took up to three days, allowing it to be presented in real-time, while also facilitating data tracing and reducing reliance on manual recording. The application can be accessed via browsers on computers and mobile devices.